ARTHROSCOPIC RECONSTRUCTION FOR CHRONIC ANTERIOR CRUCIATE LIGAMENT TEAR CAUSING PERSISTENT KNEE INSTABILITY: A CASE REPORT - Salgaonkar, Abhishek; M T, Ganesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Anterior cruciate ligament (ACL) injuries are a frequent cause of knee instability in young adults following traumatic events. Delayed presentation may lead to persistent pain, recurrent swelling, and progressive functional impairment. We present the case of a 34-year-old female who developed chronic pain and instability of the left knee after a slip-and-fall injury. Clinical evaluation, supported by magnetic resonance imaging, confirmed a complete tear of the ACL. The patient was successfully managed with arthroscopic ACL reconstruction using a quadrupled hamstring tendon autograft. Postoperatively, the patient demonstrated significant improvement in knee stability and functional outcome Lysholm knee scoring scale and IKDC scale following a structured rehabilitation program.